A Case of Large Cystic Hygroma (Advancements in Homeopathic Research, 2022)
A male child Mast. K. S. (Regn. No.: K-02007) 1 year old was brought to our clinic on 17/2/2014 for consultation by his parents from Navi Mumbai for the treatment of huge, painless, cystic swelling on right side of neck since birth. It started increasing a span of one month. Clinical Findings Large, cystic, non-tender swelling palpable on the right side of neck disfiguring the shape of face.
Keywords: child; cystic; tender; face